2023
DOI: 10.1002/ange.202304356
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Linkage Engineering of Covalent Organic Frameworks for the Oxygen Reduction Reaction

Abstract: Metal‐free covalent organic frameworks (COFs) have been employed to catalyze the oxygen reduction reaction (ORR). To achieve high activity and selectivity, various building blocks containing heteroatoms and groups linked by imine bonds were used to create catalytic COFs. However, the roles of linkages of COFs in ORR have not been investigated. In this work, the catalytic linkage engineering has been employed to modulate the catalytic behaviors. To create single catalytic sites while avoiding other possible cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…For example, Jiang et al explored COFs with various analogues, including azine, imine, amide, and oxazole linkages, and found that oxazole had the best ORR performance. 56 Song et al reported a porphyrin−bipyridinebased Co-PorBpy, where Co was incorporated with the porphyrin units to form Co−N 4 and the iminopyridine sites to form unsaturated Co−N 2 coordination. 89 Through this method, Co loading was found to be very high at 10.3 wt %, and the two different metal centers show synergistic effects, exhibiting E 1/2 of 0.84 V vs RHE.…”
Section: Cof-based Sacs For Electrocatalytic Energy Applicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Jiang et al explored COFs with various analogues, including azine, imine, amide, and oxazole linkages, and found that oxazole had the best ORR performance. 56 Song et al reported a porphyrin−bipyridinebased Co-PorBpy, where Co was incorporated with the porphyrin units to form Co−N 4 and the iminopyridine sites to form unsaturated Co−N 2 coordination. 89 Through this method, Co loading was found to be very high at 10.3 wt %, and the two different metal centers show synergistic effects, exhibiting E 1/2 of 0.84 V vs RHE.…”
Section: Cof-based Sacs For Electrocatalytic Energy Applicationsmentioning
confidence: 99%
“…There are studies focused on modifying COF linkages, metal coordination, or geometry. For example, Jiang et al explored COFs with various analogues, including azine, imine, amide, and oxazole linkages, and found that oxazole had the best ORR performance . Song et al reported a porphyrin–bipyridine-based Co-PorBpy, where Co was incorporated with the porphyrin units to form Co–N 4 and the iminopyridine sites to form unsaturated Co–N 2 coordination .…”
Section: Cof-based Sacs For Electrocatalytic Energy Applicationsmentioning
confidence: 99%
See 1 more Smart Citation